The Study of Investment Preferences of Russians on Individual Investment Accounts - Karpova, Daria; Panova, Svetlana (Journal of Reviews on Global Economics, 2018)
Individual Investment Accounts (IIAs) are assumed to be a tax incentive introduced in the Russian Federation in 2015 aimed to solve the problem of low level of private investors’ awareness of the securities market opportunities and small fraction of households’ investment in the country’s GDP. The existing evidence on such incentive is concerned mostly about the use of international tax incentives and its implementation in Russia, while rare literature provides any background on investment behaviour of the Russians, especially for 3 and more years’ time. This paper adds to this point, answering the question about the impact of major sociodemographic factors (including age, gender, marital status, education level and occupation) on the individuals’ investment preferences for long-term investment on tax-beneficial accounts, using the data from an anonymous questionnaire study conducted among 200 adult citizens of Russia.